2022
DOI: 10.1002/slct.202201546
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Fusarium Graminearum Growth and Deoxynivalenol Biosynthesis by Phenolic Compounds

Abstract: Phytopathogenic fungi infections have become a major threat to reduce crop yields and dampen human health globally. The mycelium growth inhibition method was adopted to evaluate the antifungal activity of commercially available natural and natural‐like phenols, bioassay results showed that most phenolic compounds exhibited excellent fungicidal activity against Fusarium graminearum, Rhizoctonia solani, Botrytis cinerea, Fusarium oxysporum f. sp. Vasinfectum, Sclerotinia sclerotiorum, and Magnaporthe oryzae. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Qi et al reported that salicylic acid at higher concentrations (≥0.5 mM) rather than lower concentrations could strongly reduce the production of DON ( Qi et al, 2012 ). Other studies reported a dose-dependent manner of antifungal agents including z-5, a natural-like phenolic compound ( Ma et al, 2022 ), hop essential oil ( Jiang et al, 2023 ), thyme oil ( Qi et al, 2023 ), myriocin ( Shao et al, 2021 ), etc. To examine the relationship between lipid peroxidation and DON production, correlation analysis was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Qi et al reported that salicylic acid at higher concentrations (≥0.5 mM) rather than lower concentrations could strongly reduce the production of DON ( Qi et al, 2012 ). Other studies reported a dose-dependent manner of antifungal agents including z-5, a natural-like phenolic compound ( Ma et al, 2022 ), hop essential oil ( Jiang et al, 2023 ), thyme oil ( Qi et al, 2023 ), myriocin ( Shao et al, 2021 ), etc. To examine the relationship between lipid peroxidation and DON production, correlation analysis was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…A review by Martins et al indicated that the impairment of nucleic acid biosynthesis is one of the reported antifungal mechanisms associated with phenolic compounds toward Candida species. Interference with F. graminearum DNA biosynthesis has also been observed for another phenolic compound, called Z-5 , which partly explains its inhibition of F. graminearum growth and TCTB production …”
Section: Molecular Antifungal and Antimycotoxin Mechanisms Of Stilben...mentioning
confidence: 96%
“…Interference with F. graminearum DNA biosynthesis has also been observed for another phenolic compound, called Z-5, which partly explains its inhibition of F. graminearum growth and TCTB production. 99…”
Section: Interference With Fungal Mitochondrial Functions and Involve...mentioning
confidence: 99%
See 1 more Smart Citation